Parasitic pneumonia and lung involvement - Attapon Cheepsattayakorn (2018)
Parasitic infestations demonstrated a decline in the past decade as a result of better hygiene practices and improved socioeconomic conditions. Nevertheless, global immigration, increased numbers of the immunocompromised people, international traveling, global warming, and rapid urbanization of the cities have increased the susceptibility of the world population to parasitic diseases. A number of new human parasites, such as Plasmodium knowlesi, in addition to many potential parasites, have urged the interest of scientific community. A broad spectrum of protozoal parasites frequently affects the respiratory system, particularly the lungs. The diagnosis of parasitic diseases of airway is challenging due to their wide varieties of clinical and roentgenographic presentations. So detailed interrogations of travel history to endemic areas are critical for clinicians or pulmonologists to manage this entity. The migrating adult worms can cause mechanical airway obstruction, while the larvae can cause airway inflammation. This paper provides a comprehensive review of both protozoal and helminthic infestations that affect the airway system, particularly the lungs, including clinical and roentgenographic presentations, diagnostic tests, and therapeutic approaches. © 2014 Attapon Cheepsattayakorn and Ruangrong Cheepsattayakorn.